IMPLEMENTASI STRATEGI BERBASIS MULTIPLE INTELLIGENCES PADA KEGIATAN PEMBELAJARAN EKSTRAKULIKULER DI MTs UMMUSSHABRI KENDARI - La Hadisi (Al-Izzah, 2015)
Abstract The concept of multiple intelligences which is focused on the uniqueness is always find the advantages of each child. The Purpose of this study is find out the Implementation of learning strategy in multiple intelligences practiced in Madrasah Tsanawiyah Ummusshabri, Kendari. The results indicate some facts: 1) the basic implementation of learning strategy base on multiple intelligences are orientation, content and curriculum development of KTSP; 2) the conceptual framework of multiple intelligence implementation includes three stages: the input stage, which is identification of intelligence, learning process using that multiple intelligences that includes eight intelligences, the output stage by conduct ssessment that covering three domains: cognitive, affective and psychomotor; 3) the advantages of learning strategy using multiple intelligences has been adapted to the abilities and intelligence students, so students are always enthusiastic and prevent them to get bored learning. However, the weaknesses of the strategy lies on the extra-curricular curriculum has not been fix as a reference by teachers in planning the learning proces. Key Words: Curriculum Implementation, Learning Strategies, Multiple Intelligences